PENGARUH LITERASI KEUANGAN DAN LINGKUNGAN SOSIAL TERHADAP PERENCANAAN KEUANGAN PRIBADI - Muhammad Noor Fuadi; Sri Trisnaningsih (Jurnal Proaksi, 2022)
Several survey results note that Indonesian people still carry out financial planning, in line with the diverse needs it is important to have the ability and skills to make finances. The purpose of this study was to examine and analyze the effect of financial literacy and social environment on personal financial planning for students of the UPN "Veteran" Jawa Timur Accounting Study Program. The sample used in this study found 94 respondents who were determined using the purposive sampling technique. Data analysis in this study was carried out using IBM SPSS 25 software. Based on testing and analysis, it was obtained that simultaneously (Test F) financial literacy variables and social environment variables affected the personal financial planning variable, partially (T-test) The individual financial literacy variable influences the personal financial planning variable, while the individual social environment variable does not affect the personal financial planning variable. Keywords: Financial Planning, Literacy, Social Environment